Strategic volunteer involvement: engaging the community in your mission - Ellis, Susan (Henry Stewart Talks, 2009)
How volunteer engagement connects to community relations, marketing, advocacy, client development and other goals, Fund-raising and people-raising, Stereotypes, myths and facts about who volunteers today, Designing volunteer work as first step in recruitment, The effect an organization's image has on volunteer recruitment, The connection between seeking money donors and time donors, and are these the same people?, Why people volunteer, Where to look for the right volunteers, Options for publicizing the need for volunteers, online and off, Assuring that your recruitment approach becomes the first step to both screening and eventual retention of volunteers